2021
DOI: 10.32710/tekstilvekonfeksiyon.770366
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Edge Detection Methods in the Determination of Yarn Hairiness through Image Processing

Abstract: The resolution, quality and speed of the cameras have improved enormously in recent years. The combination of camera advancements and the software industry offers significant opportunities. In this study, an image processing approach for the determination of yarn hairiness was presented. Yarn images taken under a microscope were examined in MATLAB software. Seven different edge detection algorithms were used in order to separate the hairs from the yarn body. Seven different textural properties of obtained yarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Similarly, in a previous study on Zweigle S3 hairiness, the highest correlation was found in the entropy of images processed using the Sobel technique [8]. When only ecru yarns (1-6) were evaluated instead of all yarns, higher correlation values were obtained.…”
Section: Figure 1 the Situations Before And After Image Processing Of...supporting
confidence: 64%
See 2 more Smart Citations
“…Similarly, in a previous study on Zweigle S3 hairiness, the highest correlation was found in the entropy of images processed using the Sobel technique [8]. When only ecru yarns (1-6) were evaluated instead of all yarns, higher correlation values were obtained.…”
Section: Figure 1 the Situations Before And After Image Processing Of...supporting
confidence: 64%
“…MATLAB R2018a software was used in image processing studies. The following steps were followed in image processing, respectively [8,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have successfully studied the blending of recycled PET flakes with virgin PET chips [50][51][52][53][54][55]. Recycled polyester blended yarns were successfully produced by ring, rotor and friction spinning [56][57][58][59][60][61]. Knit fabrics are commonly preferred in sportswear, casualwear and innerwear due to their outstanding comfort properties, extensible loop structure, light weight, warmth, wrinkle resistance and easycare properties [62].…”
Section: Comfort Properties Of Blend Weft Knit Fabricsmentioning
confidence: 99%
“…Bu tip ürünlerin en bilinen örneklerinden biri polietilen tereftalat (PET) şişeler olup, bu şişeler toplanıp, geri dönüştürüldükten sonra tekstil ürünlerinde %100 olarak veya karışımlar halinde "r-PET elyafı" olarak kullanılır ki bu konuyla ilgili çok sayıda çalışma bulunmaktadır. Bu çalışmaların bir kısmı; elyafın özellikleri ve eğrilebilirliği ile iplik ve kumaş özelliklerini kapsar [4,5,6,7]. Araştırmaların diğer bir kısmı ise tekstil atıklarının farklı ürünlerde kullanılmasına odaklanmıştır.…”
Section: Introductionunclassified